Consumer and business perspective on sustainable packaging of bubble tea industry in Malaysia - Sarifudin, Nur Safura; Mohd Pahme, Nur Faizah; Mohd Shuib, Ahmad Sofiyuddin; Sazali, Ahmad Noor Syahir; Soedewi, Sri (Universiti Teknologi MARA, Perak, 2025)
The growing number of bubble tea shops in Malaysia has increased consumption, resulting in packaging waste issues. This research explores the perspectives of consumers and businesses on sustainable packaging in the industry. The research uses contextual document analysis to investigate the awareness of sustainable packaging among consumers and firms through scholarly articles in scholarly journals, online articles, blogs, and forum discussions. Previous studies suggest that consumers are increasingly interested in sustainable packaging, and businesses are becoming more environmentally conscious. However, challenges such as the cost of implementation and lack of infrastructure in some areas need to be considered. This study aims to analyse the understanding and awareness of sustainable packaging design among consumers and businesses in Malaysia. This research intends to shed light on the current state of sustainable packaging in the bubble tea industry and identify potential areas for improvement to address packaging waste issues.